The impact of non-nutritive sweeteners on isolated and purified microbial cultures derived from probiotics - Alin-George Zamfir; Andreea Cristina Sandu; Marina-Ionela Ilie; Anca Ioana Scarlatescu (Amzar); Andreea Letitia Arsene; Denisa Ioana Udeanu (Amaltea Medical Publishing House, 2022)
Non-nutritive sweeteners (NNS) are a well-known substitute for table sugar with great implications in the management of various pathologies, mainly in Diabetes or Obesity. Previous studies have successfully shown that these substances are safe for human consumption, but one concern that remains is that of the impact on gut microbiota, mainly due to the complexity and diversity of the microbiome in humans. Keeping in mind that the gut microbiota contains numerous of Lactobacillus and Saccharomyces species, we simulated the microbiome by obtaining isolated microbial cultures of Saccharomyces boulardii and Lactobacillus reuteri, which we obtained two over the counter (OTC) probiotic supplements. We evaluated the bacteriostatic effect of three sweeteners (Sucralose, Saccharin, Stevia), using the successive dilution method and disc-diffusimetry on solid medium. What we sought to determine was a minimum inhibitory concentration (MIC) of each non-nutritive sweetener.